Ethics of Eros : Irigaray's re-writing of the philosophers - Chanter, Tina (Routledge, 1995)
Ethics of Eros sheds light on contemporary feminist discourse by questioning the basic distinctions and categories in feminist theory. Tina Chanter uses the work of Luce Irigaray as the focus for a critique of French and Anglo-American feminism as it is articulated in the debate over essentialism. While these two branches of feminism represent opposing views, Chanter advocates a productive exchange between the two.